Advertisement of electronic cigarettes in Italy: characteristics of online videos and the most popular promotional messages. Issue 6 (20th September 2018) - Scaioli, G; Bert, F; Martorana, M; Gili, R; Thomas, R; Gualano, M R; Siliquini, R
Abstract: Given the increasing popularity of electronic cigarettes (ECs) and a lack of regulation of EC advertising, this study aimed to analyse online videos promoting ECs to assess the main marketing messages that could influence consumers' perceptions of associated risks and benefits. A web search of EC advertising videos was performed on YouTube by using keywords related to EC promotion. An evaluation grid was used to analyse promotional messages contained in each video. The most frequent promotional messages were related to health benefits (67.7%) and to the possibility of quitting smoking (57.4%). Messages that could also be appealing to adolescents and young adults, such as those promoting the multiple flavors available and the technological improvement of ECs, were present in 41.2% and 42.7% of the videos respectively. ECs similar to traditional cigarettes in appearance were included in 52.9% of the videos. EC promotional videos address messages not only to smokers who want to quit or decrease tobacco consumption but also to nonsmokers, especially young people. The use of ECs similar to traditional cigarettes may be a gateway to tobacco cigarette use. Since EC use may represent an important public health concern, regulatory policies on EC advertising should be established.